An Analysis of Awareness and Utilization of Contraceptives Amongst Married Woman Attending a Tertiary Care Hospital in Maharashtra, India - Prachi S Koranne; Aparna R Wahane (Medsci Publications, 2014)
Introduction: It's a cross sectional observational study conducted in outpatient clinic of Obstetrics and gynecology (OBGY) of Government medical college, Akola, Maharashtra between July-December 2013. Methods: 200 married women between 20-45 yrs were interviewed with predesigned questionnaire. Effort was made to identify reasons for wide gap between the awareness and usage of birth control and spacing methods among women. Results: All women knew at least one method of contraception but 48% were using some sort of contraception. Most known method was female sterilization, least known were injectables and male sterilization. Common method chosen was female sterilization (70.8%). None adopted male sterilization. Reasons for not using contraception were desire to have child (25%), desire for boys (13.4%), worried about side effect (16.3%), opposition from family members (11.5%), felt pregnancy was naturally spaced (11.5%), no specific reasons (10.5%), couldn't avail contraceptive facilities (5.7%), inconvenient to use (5.7%). Conclusion: Educational and motivational activities from doctors and health workers are needed to promote the use of contraception.